Enhancing exercise curriculum in medical training at Loma Linda University School of Medicine - Yankee, Eva L.; Brown, Brooklin I.; Pelobello, Samuel; Rogstad, Daniel K.; Wilson, Christopher G.; Martinez, Juan J.; Blood, Arlin B.; Angeles, Danilyn M.; Mock, Andrew J.; Wilson, Sean M. (Frontiers in Education, 2025)
Exercise serves as a natural stressor on homeostatic mechanisms, providing an effective way to teach students about the physiological processes underlying stress responses and adaptation. Furthermore, long-term adaptations to chronic exercise offer important therapeutic benefits in managing a wide range of disease states. Therefore, exercise physiology and prescription are essential components of medical curricula designed to prepare physicians to counsel patients effectively. This is particularly important given that adult physical activity levels in the United States remain insufficient, especially in patients with chronic diseases. Recent guidelines provide comprehensive exercise curricula for medical education. Toward this end, we examined the current state and propose a future direction for medical exercise physiology education at Loma Linda University School of Medicine (LLUSM). We reviewed the existing preclinical and clinical medical curriculum, identified gaps, and formulated enhancements to align with recent consensus statements on exercise education in medical schools. Our unique approach builds upon our strong foundation in lifestyle medicine, integrating exercise physiology into a broader context of preventive and holistic healthcare. The analysis reveals that LLUSM dedicates 21 h to exercise within its 113-h lifestyle medicine core, supplemented by additional elective opportunities. The curriculum covers exercise effects on biochemical processes, physiological systems, and its role in disease prevention and treatment. However, gaps exist in exercise assessment and prescription skills, particularly in clinical years. To address these gaps, we propose developing a coordinated exercise thread across pre-clinical and clinical years. This includes introducing a foundational exercise physiology lecture, expanding exercise content in organ system-based pre-clinical blocks, and enhancing the clinical years to emphasize exercise assessment and prescription. The proposed curriculum aims to equip students with the knowledge and skills to confidently counsel patients on physical activity and prescribe exercise for both preventive and therapeutic purposes. We highlight the potential of this enhanced curriculum to improve students’ understanding of exercise physiology, its clinical applications, and its impact on patient wellness. By integrating exercise education throughout the medical curriculum, LLUSM aims to produce physicians who can effectively leverage physical activity as a powerful intervention for disease prevention and health promotion in healthcare delivery.